Technical Innovation Model in Improving Marketing Performance - Sutarlan, Sulistiyani (International Review of Management and Marketing, 2017)
Contradictions are still found in the research on learning and innovation, most of the researchers stated that learning orientation has a positive effect on innovation, while others argue that learning orientation negatively affects innovation. This research presents a conceptual framework of learning orientation that can improve innovation. The variables in this research were tested with 100-200 samples of bakery in Central Java. The results show that learning orientation will improve innovation, which will ultimately improve performance. This research provides recommendations for incorporating concepts related to innovation, such as communication and skills, on the relationship between learning orientation and innovation. Keywords: Learning Orientation, Communication, Skill, Performance JEL Classifications: M31, O32